FACTORS INFLUENCING SULFADOXINE-PYRIMETHAMINE RESISTANCE IN PLASMODIUM FALCIPARUM AMONG PREGNANT WOMEN IN ILORIN, NIGERIA - Obaniyi, Kehinde Adebobola; Sunday, Ojo Joseph; Said , Rukayat Olaitan; Luka, Jonathan; Salau-Deen , Badir-deen Mohammed (FUDMA JOURNAL OF SCIENCES, 2025)
Malaria remains a significant public health concern in sub-Saharan Africa, especially among pregnant women. Resistance to sulfadoxine-pyrimethamine (SP), a key drug for treatment and prevention, is rising. This study investigated the prevalence of SP resistance among pregnant women in Ilorin, Nigeria, across pregnancy trimesters and healthcare facility types, and identified influencing factors. A cross-sectional study was conducted among 764 pregnant women attending Primary, Secondary, Tertiary, and Private Health Facilities. Facilities were categorized as Primary (basic care), Secondary, Tertiary (advanced care), and Private (privately owned, with varying levels of specialisation). Resistance prevalence was defined as the percentage of pregnant women in each trimester exhibiting resistance to SP. Prevalence rates were 37.6% (first trimester), 28.9% (second trimester), 31.9% (third trimester), and 38.7% (at delivery). The highest prevalence occurred in Private Health Facilities during the first trimester (45.5%) and Secondary Health Facilities at delivery (66.7%). Multivariate regression analysis revealed that occupation, blood group, and IPTp use were the significant predictors of SP resistance. For instance, occupation was associated negatively with resistance in the first trimester: coefficient = -0.144, p = 0.027, whereas hypertension and proximity to stagnant water were significant at delivery, coefficients -0.342, p = 0.009 and -0.296, p = 0.035, respectively. These findings call for targeted malaria control strategies, considering trimester-specific risk factors and healthcare facility type. For example, improved access to IPTp and early detection of hypertension in the second and third trimesters may reduce resistance.
Keywords: Malaria; Sulfadoxine-pyrimethamine (SP) resistance; Risk factors; Pregnant women